Avian Diversity within Riparian Corridor Habitats across the Urban Environment - MacDonald, Debra J. (My University, 1998)
The objective of this research was to examine the effects of urbanization on avian diversity, specifically along riparian corridors. Bird populations vary both qualitatively and quantitatively among habitats and urbanization has had a visible impact on those habitats. This research attempted to quantify the effects of urbanization on avian diversity by comparing urbanized habitat with relatively undisturbed habitat along nine riparian corridors within an area comprised of both parkland and residential neighborhoods. Habitat parameters and bird species data were collected for 86 sites over a two year period. I tested three hypotheses as follows: (1) that species diversity is higher in less disturbed park habitat; (2) that foraging and nesting guild diversity is higher in less disturbed habitat; and (3) that tropical migrant abundance is higher in less disturbed habitat. Habitat data were analyzed to ensure that the four major categories of habitat (Federal Park, County or Local Park, Edge and Developed) reflected differences in disturbance factors. These four categories, as well as the individual measures of disturbance, were used in my examination of bird species data. Species richness was used to estimate species diversity. In addition, species data were categorized into guilds, based on foraging and nesting behaviors. Use of foraging and nesting guilds was based on previous work by Willson (1974) and DeGraaf and Wentworth (1981), in which guilds were analyzed in the same way that species are typically analyzed. Species data for tropical migrants were also analyzed. Tropical migrant abundance was compared across the four habitat categories. There were no statistically significant correlations between habitat variables and species richness. In addition, there was no significant difference in species richness between major habitat categories. Thus the null hypothesis that there would be no difference in species richness between habitats was not rejected. Analysis of guild diversity, however, supported the hypothesis that foraging and nesting guild diversity would be higher in less disturbed habitat. The difference in the results for the first and second hypotheses may indicate that although bird diversity remains at a constant level along the riparian corridor, the population changes to become more functionally homogenous. The third hypothesis, that tropical migrant abundance is higher in less disturbed habitat, was supported by analysis of variance of the proportion of tropical migrant detections across the 4 major habitat categories. Detections of tropical migrants were highest in the federal park habitats, whether expressed as a number of detections or as a proportion of total detections. They were lower in County and local park habitat and significantly lower outside of park habitats. Thus, the null hypothesis, that tropical migrant abundance would be the same across habitats, was rejected. This study was a broad look at a very complex subject. Species specific research may be necessary to determine how the various factors of urbanization affect the avian population. In addition, further research is needed to determine the role undisturbed habitat plays for bird populations within urban areas.